On the Method of Design Drift-Ice Concentration and Floe Area for New-Energy Structures in Ice-Infested Nearshore Areas of the Bohai Sea, China - Li, Zhijun; Xiu, Yuanren; Wang, Qingkai; Li, Ge; Lu, Peng; Zhong, Shan; Chen, Xue (Frontiers in Energy Research, 2022)
To provide basic drift-ice parameters for new-energy structures in ice-infested nearshore waters, an estimation method of the design drift-ice concentration and floe area was established. A total of 700 satellite images in winters from 2010 to 2021 were used to obtain the drift-ice concentration and floe area from 26 sites in the Bohai Sea. The floe area with 90% cumulative probability was selected as the characteristic floe area in each satellite image. Furthermore, the water temperature threshold ranging from −1.6 °C to −0.5 °C was adopted by considering the drift-ice freezing/melting states because of different salinity values in nearshore waters. The upper limit values of the ice concentration and characteristic floe area at the lowest water temperature of −1.6 °C were finally used as the design drift-ice indexes. The maximum design ice concentrations (floe area) in the Liaodong Bay, Bohai Bay, and Laizhou Bay were 96% (0.43 km2), 91% (0.39 km2), and 87% (0.29 km2), respectively. The design ice concentration at the bay bottom was higher than that near the mouth. The design floe area in the Liaodong Bay and Bohai Bay increased with latitudes, but the trend was opposite in the Laizhou Bay. The method developed in the current study has universal applicability, which can be extended to other ice-cover waters and specific structure designs by adjusting the cumulative probability threshold and the water temperature threshold.